2019
DOI: 10.1111/jace.16625
|View full text |Cite
|
Sign up to set email alerts
|

Reactive flash sintering of powders of four constituents into a single phase of a complex oxide in a few seconds below 700°C

Abstract: Recent work on reactive flash sintering of powders of two oxides, bismuth and of iron oxide, into pure single phase bismuth ferrite, which was accomplished in a few seconds at low furnace temperatures, is expanded to four constituents, alumina, lithia, zirconia, and lanthana, to produce reasonably dense polycrystals of a predominantly single phase, cubic LLZO(Al). Transformation and sintering occur concurrently at a furnace temperature near 700°C, in ambient atmosphere, in just a few seconds. The process may s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
38
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 24 publications
1
38
0
Order By: Relevance
“…3 , an amorphous precursor powder to form Li 0.5 La 0.5 TiO 3 , and NaNbO 3 + KNbO 3 Na 0.5 K 0.5 NbO 3 . [4][5][6]8,9 Additionally, this work demonstrates the reduction of CuO to form Cu 2 O during stage II. Systems that transform during stage III include Al 2 O 3 + TiO 2 → Al 2 TiO 5 and our previous work on the reduction of Mn 2 O 3 → Mn 3 O 4 .…”
Section: Introductionmentioning
confidence: 62%
See 2 more Smart Citations
“…3 , an amorphous precursor powder to form Li 0.5 La 0.5 TiO 3 , and NaNbO 3 + KNbO 3 Na 0.5 K 0.5 NbO 3 . [4][5][6]8,9 Additionally, this work demonstrates the reduction of CuO to form Cu 2 O during stage II. Systems that transform during stage III include Al 2 O 3 + TiO 2 → Al 2 TiO 5 and our previous work on the reduction of Mn 2 O 3 → Mn 3 O 4 .…”
Section: Introductionmentioning
confidence: 62%
“…Additionally, rapid synthesis at low furnace temperatures reduces the loss of volatile precursors and allows for the synthesis of materials that are difficult to produce conventionally (high temperatures, long hold times). [4][5][6] The most common approach to reactive flash sintering is to combine oxide precursors and flash them. Our previous work demonstrated that reactive flash sintering can also be applied in reduction reactions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study has demonstrated the flash sintering of ceramic films with varying thicknesses in the range of sub‐millimeters . Other efforts include reactive flash sintering for rapid chemical synthesis of complex single phase oxides . However, flash sintering performed on thin films has yet to be demonstrated and could open new opportunities in various solid‐state device applications, such as fuel cells and batteries.…”
Section: Introductionmentioning
confidence: 99%
“…19 Other efforts include reactive flash sintering for rapid chemical synthesis of complex single phase oxides. 20,21 However, flash sintering performed on thin films has yet to be demonstrated and could open new opportunities in various solid-state device applications, such as fuel cells and batteries. Hence, the present work is to demonstrate the feasibility of performing a…”
Section: Introductionmentioning
confidence: 99%